Action Research on the Professional Learning Community (PLC) for Chinese Language Transition Between Primary and Secondary Schools in Singapore: 新加坡中小学华文衔接的教师共同体行动研究 - Dong Yan (Published by Confucius Institute UNS, 2026)
Based on the demand for the